2017
DOI: 10.1108/mf-07-2015-0185
|View full text |Cite
|
Sign up to set email alerts
|

Board and audit committee effectiveness in the post-ASX Corporate Governance Principles and Recommendations era

Abstract: Purpose The purpose of this paper is to contribute to the corporate governance literature by examining the aggregate effect of board and audit committee characteristics on earnings management practices, particularly in the period following the introduction of the second edition of the Australian Securities Exchange (ASX) Corporate Governance Principles and Recommendations. Design/methodology/approach This paper begins by embarking on an extensive review of extant empirical research on boards of directors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 89 publications
0
19
1
Order By: Relevance
“…The information gap resulting from the separation of corporate ownership and management necessitated forms of control and monitoring both internally and externally (Young, 2000;Weir et al, 2002): internally through the board of directors and its committees, and externally through the report of the external auditors as well as through market control (Safari, 2017;Ali et al, 2018). Recent well-known international corporate failures and collapses, following the global financial crisis of the last decade, have urged global professional bodies for inclusive regular restructuring and reform of the systems of internal control and governance, emphasising the role of auditors and stressing the importance of audit quality (Kilgore et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The information gap resulting from the separation of corporate ownership and management necessitated forms of control and monitoring both internally and externally (Young, 2000;Weir et al, 2002): internally through the board of directors and its committees, and externally through the report of the external auditors as well as through market control (Safari, 2017;Ali et al, 2018). Recent well-known international corporate failures and collapses, following the global financial crisis of the last decade, have urged global professional bodies for inclusive regular restructuring and reform of the systems of internal control and governance, emphasising the role of auditors and stressing the importance of audit quality (Kilgore et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Different results are obtained by Al-Thuneibat, Al-Angari, and Al-Saad (2016) revealed that EM practices were not significantly affected by the AC, internal audit and the board of directors. However, AC independent and internal audits have a negative direction on EM practices Other research conducted in Australian stock exchange by Safari (2017) shows that a high level of compliance with board and AC principles influences lower EM practices. Kazemian and Mohd, (2015) stated that agency theory is the basis for EM practice because there is a separation of ownership and control so that the manager will use financial statements that are in line with manager needs.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…AC size is importance as for an AC to be properly functioning in organisation the adequate manpower is required to ensure all matters and issues are being resolved including any of the issues arising from the internal control and financial reporting (SCM, 2017). Prior research into the effects of the ACs on the audit quality has returned mixed results (Akhtaruddin & Haron, 2010;Al-Okaily & Naueihed, 2019;Martinov-Bennie, Soh, & Tweedie, 2015;Safari, 2017).…”
Section: Literature Review Prior Research On Audit Committeementioning
confidence: 99%